Maternal and fetal outcomes of pregnant women with bacterial vaginosis - Ng, Beng Kwang; Chuah, Joo Ngor; Cheah, Fook Choe; Mohamed Ismail, Nor Azlin; Tan, Geok Chin; Wong, Kon Ken; Lim, Pei Shan (Frontiers in Surgery, 2023)
Background: Bacterial vaginosis (BV) is a common infection in women of reproductive age group because of vaginal dysbiosis. The impact of BV during pregnancy is still not well defined. The objective of this study is to assess the maternal and fetal outcomes of women diagnosed with BV at antenatal clinic visits. Materials and Methods: A prospective cohort study over one-year duration was conducted from December, 2014 until December, 2015, involving 237 women who presented antepartum with abnormal vaginal discharge, preterm labour or preterm prelabour rupture of membrane suspected to have BV, between 22- and 34-weeks period of gestation. Vaginal swabs were sent for culture and sensitivity, BV® Blue testing and PCR for Gardnerella vaginalis (GV). Results: BV was diagnosed in 24/237 (10.1%) cases. The median gestational age was 31.6 weeks. GV was isolated from 16 out of 24 (66.7%) in the BV positive group. There was a significantly higher preterm birth rate, below 34 weeks (22.7% vs. 6.2%, p=0.019) in women with BV. There was no statistically significant difference in maternal outcome such as clinical chorioamnionitis or endometritis. However, placental pathology revealed more than half (55.6%) of women with BV had histologic chorioamnionitis. Neonatal morbidity was significantly higher with exposure to BV, with a lower median birth weight, higher rate of neonatal intensive care unit admission (41.7% vs. 19.0%, p=0.010), increased intubation for respiratory support (29.2% vs. 7.6%, p=0.004) and respiratory distress syndrome (33.3% vs. 9.0%, p=0.002). Conclusion: More research is needed to formulate guidelines for prevention, early detection and treatment of BV during pregnancy to reduce the adverse outcomes associated with histologic chorioamnionitis and preterm birth.